Australosagola, a new genus of pselaphine beetles from southern Australia (Coleoptera, Staphylinidae, Pselaphinae, Faronitae) with descriptions of seven new species - Su-Ho Choi; Donald S. Chandler; Jong-Seok Park (ZooKeys)
The new Australian genus, Australosagola, gen. nov. supertribe Faronitae, is described with seven new species and three new combinations for species previously assigned to Sagola Sharp, 1874. This genus includes Australosagola tasmaniae (Lea, 1911), comb. nov. (type species), A. rugicornis (Oke, 1932), comb. nov., A. helenae (Oke, 1925), comb. nov., A. minsangi sp. nov., A. minhoi sp. nov., A. jiwooki sp. nov., A. sunheei sp. nov., A. doohyungi sp. nov., A. jungjooni sp. nov., and A. yongsooni sp. nov. A key, illustrations of major diagnostic characters, habitus images, and distribution maps are provided.